Clinical Responses to Rituximab in a Case of Neuroblastoma with Refractory Opsoclonus Myoclonus Ataxia Syndrome - Samin Alavi; Ali Kord Valeshabad; Borhan Moradveisi; Ali Aminasnafi; Mohammad Taghi Arzanian (Case Reports in Oncological Medicine)
Opsoclonus myoclonus ataxia syndrome (OMS) is a rare neurologic syndrome. In a high proportion of children, it is associated with neuroblastoma. The etiology of this condition is thought to be immune mediated. In children, immunotherapy with conventional treatments such as corticosteroids, intravenous immunoglobulin, adrenocorticotropic hormone, and even antiepileptic drugs has been tried. Recently rituximab has been used safely for refractory OMS in children with neuroblastoma. Our patient was a 3.5-year-old girl referred for ataxia and dancing eye movements starting since 1.5 years ago. She was diagnosed with neuroblastoma on imaging studies on admission. The OMS was refractory to surgical resection, chemotherapy, corticosteroids, and intravenous immunoglobulin. Patient received rituximab simultaneously with chemotherapy. The total severity score decreased by 61.1% after rituximab. Patient's ataxia markedly improved that she was able to walk independently after 6 months. Our case confirmed the clinical efficacy and safety of rituximab in a refractory case of OMS.